Optimization of ultrasound-assisted parthenolide extraction from Tarchonanthus camphoratus leaves using response surface methodology: HPTLC and cytotoxicity analysis - Nasir A. Siddiqui; Perwez Alam; Adnan J. Alrehaily; Ali S. Alqahtani; Ali Akhtar; Tawfeq A. Alhowiriny; Omer M. Almarfadi; Ramzi A. Mothana (Arabian Journal of Chemistry, 2021)
The aim of this study was to optimize the ultrasonication method for efficient extraction of parthenolide from Tarchonanthus camphoratus leaves using Box–Behnken design for response surface methodology (RSM) and then to validate the method by high performance thin layer chromatography (HPTLC). RSM was used to optimize the extraction parameters, i.e., temperature (25–45 °C), time (35–55 min), and liquid-to-solid ratio (16–24 mL/g), to maximize parthenolide yield. Quantitative estimation of parthenolide in ethanol extract (TCEE) of T. camphoratus leaves was conducted to check the effect of all the three variables and validated by HPTLC method using n-hexane and ethyl acetate (3:1, v/v) as mobile phase. A quadratic polynomial model was found to be most suitable with regard to R (parthenolide yield), with R2/%CV = 0.9973/0.4557. The adjusted R2, predicted R2, and signal-to-noise ratio for R were 0.9937, 0.9870, and 47.94, respectively, indicating a high level of tie-in with adequate signal. There was a strong linear correlation between the predicted and experimental R values (R2 = 0.9973). In TCEE, parthenolide was detected with a Rf value of 0.15 at λmax = 590 nm. The optimized ultrasonic extraction produced 1.010% ± 0.04 %w/w with the following extraction parameters: 38.8 °C (M1), 50-min extraction time (M2), and 20.4-mL/g liquid-to-solid ratio (M3). The obtained results of optimization also endorsed by cytotoxicity results (CC50125.47 μg/mL) on human hepatoma cells (HuH7).